Analysis of Language Politeness Between Students and Lecturers through Whatsapp - Agus Qowiyuddin; A’yuniatuz Zahrah; Moch. Mushoniful A. (Puitika)
A relationship between students and lecturers requires communication, both on and off campus. This communication should remain within the boundaries of politeness values, however spoken in semi- formal situations. The existence of social media as a technological development also influences communication between students and lecturers. This research examines speaking styles and politeness values used by students in communicating with lecturers through WhatsApp. The aim of this research is to describe and analyze language politeness used by students when communicating with lecturers via WhatsApp, making descriptions and analyzing deviations from the principles of language politeness used by students when communicating with lecturers via WhatsApp. The data source for this research is a chat application WhatsApp. The research data is in the form of student speech which is used to communicate with lecturers via WhatsApp. This data is used to collect information so that it can be analyzed. Data collection techniques use observation methods, note- taking techniques and interviews. Data analysis was carried out using qualitative methods. Based on the analysis of research results, it was found that there were still many students' speech to lecturers via the WhatsApp application that did not meet politeness values. In this speech, there are still many deviations in politeness in the form of the use of slang, discussions outside the lecture context, impolite ways of expressing intentions, and inappropriate use of paralinguistic aspects.